Academic productivity as perceived by Malaysian academics - Hassan, Aminuddin; Tymms, Peter; Ismail, Habsah (Routledge, 2008)
The purpose of this research is to explore the perspectives of Malaysian academics in relation to academic productivity and some factors affecting it. A large scale online questionnaire was used to gather information from six public universities. The most productive role in the eyes of the academics was found to be teaching. with research and administration coming second and third, respectively. Several factors were found to be related to productivity and some of these have policy implications. The universities themselves differed markedly and research productivity was related to the amount of time available, and linked negatively to the teaching load.